Patriot Ekspatriat: Imajinasi dan Aksi Anti-Kolonialisme dan Nasionalisme Asia Tenggara - Wildan Sena Utama (Jurnal Kajian Wilayah, 2014)
This article explores another variant of the emergence of the nationalism and anti colonialism idea. In the discourse of nationalism and anti-colonialism, much of attention from historians solely allocate to the rooted aspect of the formation of the nation, while there is a forgotten that the nationalism awareness and the anti-colonial sensitivity also can sprout from the mobility or travel of the community or individual far beyond the homeland. This article wants to observe the mobile aspects of the imagination and the action of anti-colonialism and nationalism from this type of individuals, called expatriate patriots, which was invented and awakened from their relationship that they interlaced during their odyssey in Europe. I argue, despite of their networks, interactions, experiences, model and method of actions were different, however, their impact on the discourse of nation formation was no doubt very important.Keywords: expatriate patriots, anti-colonialism, nationalism, and travel.